Role of the Exosome Secretion Machinery in Ovarian Carcinoma: In Vitro and In Vivo Models. (30th May 2020) - Broner, Esther Channah; Onallah, Hadil; Tavor Re'em, Tali; Davidson, Ben; Reich, Reuven
Abstract : Objective . We recently reported on the expression and clinical role of molecules that mediate exosome secretion in high-grade serous carcinoma. In the present study, the biological role of these molecules was analyzed. Methods . OVCAR8 and ES-2 ovarian carcinoma cells were studied using a combination of CRISPR/Cas9 technology and two 3D in vitro models—spheroids emulating effusions and alginate scaffolds representing solid lesions. Isolation of exosomes was validated by electron microscopy. TSAP6, NSMASE2, RAB27A, and RAB27B mRNA and protein levels were analyzed using qRT-PCR and Western blotting, respectively. Tumor aggressiveness was studied in vitro using scratch assay, invasion assay, and matrix metalloproteinase (MMP) activity assay and in vivo using a mouse model. Results . In OVCAR8 cells, mRNA expression of TSAP6 and RAB27A was significantly higher in spheroids compared to scaffolds, whereas the opposite was true for NSMASE2 mRNA. In ES-2 cells, TSAP6 and RAB27B mRNA expression was significantly higher in spheroids versus scaffolds. In addition, nSMase2 and TSAP6 protein expression was significantly higher in scaffolds compared to spheroids. CRISPR-edited cells with silencing of NSMASE2, TSAP6, and RAB27A/B had reduced migration, invasion, and MMP activity. Additionally, knockout (KO) of these molecules resulted in significantly diminished exosome secretion. In vivo assay showed that when injected to mice, OVCAR8 RAB27A/B KO cells, as opposed to control OVCAR8 cells, did not form ascites or visible tumor lesions and had reduced MMP expression. Conclusion . The present study provides evidence that different models for culturing ovarian carcinoma cells affect the expression of molecules mediating exosome secretion and that these molecules have a tumor-promoting role. Silencing these molecules may consequently have therapeutic relevance in this cancer.